Structural intersectionality and Indigenous Canadian youth who trade sex: understanding mobility beyond the trafficking model. (September 2019) - Ting, David Allan Jun-Rong; Showden, Carisa R
Indigenous young people in Canada who trade sex frequently move locations as part of their survival tactics in negotiating the myriad vulnerabilities they face. Both Canadian law and social activists label all such mobility "trafficking", which conceals the ways in which Indigenous youth are forced by structural factors beyond their control to be mobile to survive. Two politically opposed frameworks have been offered for understanding sex trading by Indigenous youth. While each explains some vulnerabilities faced by these young people, both overlook others. We posit mobility and sex trading as strategic responses to the material and ideological conditions faced by Indigenous young people, but strategic responses rooted in vulnerability and rife with exploitation. Ultimately, we argue that mobility is a response to vulnerability rather than its source.